Compact quad‐channel high‐temperature superconducting diplexer based on stub‐loaded square ring resonator. Issue 7 (14th March 2019) - Guan, Xuehui; Gui, Ping; Ren, Baoping; Zhang, Xiaoyan
ABSTRACT: A compact quad‐channel high‐temperature superconducting diplexer based on stub‐loaded square ring resonator (S‐LSRR) is proposed. The proposed resonator consists of a square ring with symmetrically loaded two open‐circuited stubs and provides four resonant modes for quad‐channel applications. Even‐ and odd‐mode methods are applied to analyze the S‐LSRR. Analytical study shows that four resonant modes of one S‐LSRR can be designed in two pairs and applied to construct two of four channels of the designed diplexer. A square patch is added to the resonator for providing an additional parameter to tune the resonant modes. Based on the proposed resonator, a quad‐channel diplexer with center frequencies of 2.4, 3.2, 3.9, and 5.6 GHz is designed. For demonstration, the diplexer is fabricated on 2‐in‐diameter 0.5 mm‐thick MgO wafer with double sided YBa2 Cu3 Oy films and measured at 77 K. Good agreement between the simulation and measurement is obtained. The diplexer has a compact size of 0.25 λ g × 0.45 λ g, where λ g is guided wave length at the center frequency of first channel.